What the high school students say about mathematics homework - Fransiskus Magnis Pastoriko; Kana Hidayati; Rasmuin Rasmuin (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2019)
Homework had become a tradition in teaching and learning mathematics in school. Even so, in Indonesia, there is not enough research on homework. Our research is conducted to investigate high school students’ views on homework and to provide the basis for further research on homework in Indonesia. In this research, we use exploratory-descriptive qualitative to explore and describe the students’ view of homework. We collected the data from 124 high school students by using the structured interview conducted via online form. The data were analyzed by using the thematic analysis. Based on our results, we found that (1) students know that mathematics homework can help them with their academic achievement and their attitudes toward their studies, (2) mathematics homework is not high on their priority, (3) it makes them tired physically and mentally, and (4) students argue that mathematics problems are better to be solved in the class where they can ask the teacher. We also found their difficulties in doing their homework, such as (1) lack of knowledge (2) their teachers do not give them the necessary ‘tools’ to solve the problems, (3) they can’t ask for helping hands if they can’t solve the problems (4) some emotional problems such as motivation, and (5) other priorities are higher on their list.